"Thymus algeriensis" and "Thymus fontanesii": chemical composition, in vivo antiinflammatory, pain killing and antipyretic activities: a comprehensive comparison - Sobeh, Mansour; Rezq, Samar; Cheurfa, Mohammed; Abdelfattah, Mohamed A. O.; Rashied, Rasha M. H.; El-Shazly, Assem; Yasri, Abdelaziz; Wink, Michael; Mahmoud, Mona Fouad (Biomolecules, 2020)
This study aimed to investigate the chemical composition, and evaluate the antioxidant, anti-inflammatory, anti-pyretic, and the analgesic properties of methanol extracts from the leaves of Thymus algeriensis and Thymus fontanesii (Lamiaceae). Thirty-five secondary metabolites were characterized in both extracts using HPLC-PDA-ESI-MS/MS. Phenolic acids, mainly rosmarinic acid and its derivatives, dominated the T. algeriensis extract, while the phenolic diterpene carnosol and the methylated flavonoid salvigenin, prevailed in T. fontanesii extract. Molecular docking study was carried out to estimate the anti-inflammatory potential and the binding affinities of some individual secondary metabolites from both extracts to the main enzymes involved in the inflammation pathway. In vitro enzyme inhibitory assays and in vivo assays were used to investigate the antioxidant and anti-inflammatory activities of the extracts. Results revealed that both studied Thymus species exhibited antioxidant, anti-inflammatory, analgesic, and antipyretic effects. They showed to be a more potent antioxidant than ascorbic acid and more selective against cyclooxygenase (COX-2) than diclofenac and indomethacin. Relatively, the T. fontanesii extract was more potent as COX-2 inhibitor than T. algeriensis. In conclusion, Thymus algeriensis and Thymus fontanesii may be interesting candidates for the treatment of inflammation and oxidative stress-related disorders.
Gesehen am 22.07.2020